2019
DOI: 10.1126/sciadv.aaw9770
|View full text |Cite
|
Sign up to set email alerts
|

Correlated insulating and superconducting states in twisted bilayer graphene below the magic angle

Abstract: The emergence of flat bands and correlated behaviors in "magic angle" twisted bilayer graphene (tBLG) has sparked tremendous interest, though many aspects of the system are under intense debate. Here we report observation of both superconductivity and the Mott-like insulating state in a tBLG device with a twist angle of ~0.93º, which is smaller than the magic angle by 15%. At an electron concentration of ±5 electrons/moiré unit cell, we observe a narrow resistance peak with an activation energy gap ~0.1 meV, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
146
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(151 citation statements)
references
References 51 publications
3
146
0
2
Order By: Relevance
“…Spurred by the discovery of a plethora of insulating and superconducting states in twisted bilayer graphene (TBG) [1,2], a growing stream of experimental evidence points to the generic emergence of correlated electronic behavior in various moiré heterostructures [3][4][5][6][7][8][9][10][11][12]. The basic mechanism that gives rise to strongly-enhanced correlation effects in these materials is the formation of long-wavelength moiré patterns with (almost) flat lowenergy bands whose narrow bandwidth becomes comparable to the otherwise negligible energy scale of the electronic interactions [13][14][15].…”
mentioning
confidence: 99%
“…Spurred by the discovery of a plethora of insulating and superconducting states in twisted bilayer graphene (TBG) [1,2], a growing stream of experimental evidence points to the generic emergence of correlated electronic behavior in various moiré heterostructures [3][4][5][6][7][8][9][10][11][12]. The basic mechanism that gives rise to strongly-enhanced correlation effects in these materials is the formation of long-wavelength moiré patterns with (almost) flat lowenergy bands whose narrow bandwidth becomes comparable to the otherwise negligible energy scale of the electronic interactions [13][14][15].…”
mentioning
confidence: 99%
“…where 0 is the intrinsic diffusivity of copper, E is the activation energy of copper, T is the growth temperature in Kelvin, is the Boltzmann constant. From literature, 0 = 5.6 × 10 −7 2 / and = 0.92 5,6. Hence, the diffusion coefficient of carbon into copper at our growth temperature (1050 ℃) is 175 nm2/s.…”
Section: Supplementary Textmentioning
confidence: 79%
“…by rotation of 2 stacked SLG sheets to form a Moiré superlattice. For instance, Cao et al [7] showed that MATBG with  = 1.16° exhibits zero resistance at Tc = 0.14 K, whereas an angle  = 1.05° has zero resistance at Tc ~ 1.2 K. More recently, several research groups have discovered a superconducting state in MATBG [8][9][10][11], including studies of MATBG at high-pressures (up to P = 4 GPa), as well as in trilayer graphene/boron nitride Moiré superlattices [12].…”
Section: Introductionmentioning
confidence: 99%